Why is life expectancy in England and Wales 'stalling'? - Hiam, L; Harrison, D; McKee, M; Dorling, D (BMJ Publishing Group, 2018)
Several independent analyses, by both epidemiologists and actuaries, have concluded that the previous rate of improvement of life expectancy in England and Wales has now slowed markedly, and at older ages may even be reversing. However, although these findings have led the pension industry to reduce estimates of future liabilities, they have failed to elicit any significant concern in the Department of Health. In this essay, we review the evidence on changing life expectancy, noting that the problems are greatest among older women. We then estimate the gap between what life expectancy is now and what it might have been had previous trends continued. At age 85 this is 0.34 years for women and 0.23 for men. We argue that recent changes cannot be dismissed as a temporary aberration. While the causes of this phenomenon are contested, there is growing evidence to point to the austerity policies implemented in recent years as at least a partial explanation. We conclude by calling for a fully independent enquiry to ascertain what is happening to life expectancy in England and Wales and what should be done about it.